Modulation of Hypoxia-Induced Pulmonary Vascular Leakage in Rats by Seabuckthorn (Hippophae rhamnoides L.). (15th March 2011) - Purushothaman, Jayamurthy; Suryakumar, Geetha; Shukla, Dhananjay; Jayamurthy, Himani; Kasiganesan, Harinath; Kumar, Rajesh; Sawhney, Ramesh Chand
Abstract : Cerebral and pulmonary syndromes may develop in unacclimatized individuals shortly after ascent to high altitude resulting in high altitude illness, which may occur due to extravasation of fluid from intra to extravascular space in the brain, lungs and peripheral tissues. The objective of the present study was to evaluate the potential of seabuckthorn (SBT) ( Hippophae rhamnoides L.) leaf extract (LE) in curtailing hypoxia-induced transvascular permeability in the lungs by measuring lung water content, leakage of fluorescein dye into the lungs and further confirmation by quantitation of albumin and protein in the bronchoalveolar lavage fluid (BALF). Exposure of rats to hypoxia caused a significant increase in the transvascular leakage in the lungs. The SBT LE treated animals showed a significant decrease in hypoxia-induced vascular permeability evidenced by decreased water content and fluorescein leakage in the lungs and decreased albumin and protein content in the BALF. The SBT extract was also able to significantly attenuate hypoxia-induced increase in the levels of proinflammatory cytokines and decrease hypoxia-induced oxidative stress by stabilizing the levels of reduced glutathione and antioxidant enzymes. Pretreatment of the extract also resulted in a significant decrease in the circulatory catecholamines and significant increase in the vasorelaxation of the pulmonary arterial rings as compared with the controls. Further, the extract significantly attenuated hypoxia-induced increase in the VEGF levels in the plasma, BALF (ELISA) and lungs (immunohistochemistry). These observations suggest that SBT LE is able to provide significant protection against hypoxia-induced pulmonary vascular leakage.